2004
DOI: 10.1515/hf.2004.085
|View full text |Cite
|
Sign up to set email alerts
|

Artificial weathering of tropical woods. Part 2: Color change

Abstract: This paper describes the change in diffuse reflectance Fourier transform infrared (DRIFT) and ultraviolet-visible (UV-Vis) diffuse reflectance spectra of the following eight tropical woods during artificial weathering up to 600 h in relation to their color changes, especially to yellowing: Amnurana acreana, Acacia auriculiformis, Dipterocarpus spp., Eucalyptus marginata, Eucalyptus robusta, Shorea spp. and Tabebuia spp. with relatively high and low specific gravity. For A. acreana, A. auriculiformis, Dipteroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 15 publications
4
24
0
Order By: Relevance
“…Sample Bw underwent yellowing to the greatest extent during the weathering process. Previous studies have shown that a quick change in color occurs in the rapid phase of the photochemical reaction (Arnold et al 1991;Müller et al 2003;Kishino and Nakano 2004;Baysal et al 2014). This kind of reaction tends to reach a point of equilibrium because of the slow diffusion of oxygen and the free radicals (which are necessary for the reaction) from the material surface to its interior (Arnold et al 1991).…”
Section: Color Changes During Accelerated Weatheringmentioning
confidence: 99%
“…Sample Bw underwent yellowing to the greatest extent during the weathering process. Previous studies have shown that a quick change in color occurs in the rapid phase of the photochemical reaction (Arnold et al 1991;Müller et al 2003;Kishino and Nakano 2004;Baysal et al 2014). This kind of reaction tends to reach a point of equilibrium because of the slow diffusion of oxygen and the free radicals (which are necessary for the reaction) from the material surface to its interior (Arnold et al 1991).…”
Section: Color Changes During Accelerated Weatheringmentioning
confidence: 99%
“…Pietta (2000) found that phenolics in plant extractives absorb free radicals and have effective antioxidant activity. Kishino and Nakano (2004) attributed the improved antioxidant ability of thermally modified wood to the increased phenol content and the higher concentrations of stable phenoxyl-free radicals. Hence, it is likely that the presence of phenolics extractives had a protective effect against the degradation of thermally modified Scots pine.…”
Section: Weight Lossmentioning
confidence: 99%
“…It is possible to perceive differences of about 3.8 units of AE* [17,192]. Thus, the difference of AE between heat-treated and untreated wood surfaces during artificial sunlight irradiation is due to the difference in their initial colors.…”
Section: Testing Materials and Artificial Sunlight Irradiation(uv-vismentioning
confidence: 99%
“…Pandey [44] reported that the color changes on wood surfaces were mainly due to the formation of C=O groups as a result of the photodegradation of lignin. Masanori and Tokato [192] suggested that the formation of non-conjugated carbonyl functional group played an important role in the color change in woods for which Ab* increased but not for woods for which Àb* decreased. However, it can be observed from the color results shown in As stated in Section 4.5, the degradation of lignin by weathering can increase the content of other components on wood surface and consequently make the surface more hydrophilic.…”
Section: Chemical Changes Due To Irradiation Without Water Spray A) Fmentioning
confidence: 99%